COMMUNITY-ACQUIRED PNEUMONIA IN HIV-INFECTED SUBJECTS: MICROFLORA, ANTIBIOTIC RESISTANCE: DEPENDENCE ON THE LEVELS OF CD4 LYMPHOCYTES - D. N. Akusheva; О. Е. Khokhlova; V. V. Kamshilova; A. I. Motova; О. V. Peryanova; A. A. Upirova; N. К. Potkina; Tatsuo Yamamoto (Медицинская иммунология, 2019)
Purulent inflammatory diseases of various types and etiology comprise major causes of death among the HIV-infected individuals. The purpose of this work was to determine a variety of communityacquired pathogens causing pneumonia, their antibiotic resistance profiles, and dependence on the CD4 lymphocyte levels, as well as identification of methicillin-resistant Staphylococcus aureus species and their molecular genetic characteristics in HIV-infected patients from the Krasnoyarsk City. Over the period of 2012 to 2016, we have examined 152 HIV-infected patients at the Clinical Pulmonology Department with a verified diagnosis of community-acquired pneumonia. Sputum specimens, bronchoalveolar lavage, pleural fluid, washings, pleural pus, as well as nasal and pharyngeal smears were studied for microflora, and blood tests for sterility were performed in these patients, by means of bacteriological techniques. Antibiotic sensitivity was determined by the disc diffusion method; drug sensitivity of staphylococci was performed by screening, PCR technique, serial dilution in semi-solid medium, according to the CLSI and EUCAST recommendations. PCR, M-PCR, and gene sequencing were applied for genotyping and determination of their genetic features. The results were processed with WHONET digital program (WHO). The significance level was p < 0.05. During the entire study period, the yeast-like fungi of Candida genus (30.4 and 35.6%) were consistently isolated from HIV-infected patients. These microorganisms were isolated in a pure cultures at etiologically significant amounts from one-third of the HIV-infected cohort. At the same time, they formed active associations, mostly with Enterobacteriaceae family members. At the same time, Candida fungi were most frequently detected in the lower respiratory tract of those HIV-infected persons who showed severe immunodeficiency (CD4 cell levels < 200 cells/µl). We have also isolated non-fermenting Gram-negative bacteria (12.9%), staphylococci (8.9%), and Enterobacteriaceae (4.4%). The microorganisms were characterized by polyresistance to antimicrobial agents. The MRSA clone circulating in the HIV-infected cohort was characterized as ST239/spa3(t037) /agr1/SCCmecIII.1.1.2 (IIIA)/coaIV/tst+ with high virulence and multiresistance levels. Hence, we have found a number of poly-resistant microorganisms playing a role for development of community-acquired pneumonia in HIV-infected patients, i.e., Candida spp, Gram-negative microorganisms, MRSA, often presenting a component of microbial associations. Candida fungi were detected most often in the HIV-infected individuals with severe immunodeficiency, at the CD4 level of < 200 cells/µl. High detection frequency of such microflora requires some modifications of antimicrobial therapy in HIV-infected subjects affected by the community-acquired pneumonia.